Pengaruh Asean Corporate Governance Scorecard dan Struktur Kepemilikan Terhadap Asimetri Informasi Pada Perusahaan Kelompok Kompas 100 di Bursa Efek Indonesia - Pormawati Siringo; Sri Yuni; Leliana Maria Angela (JEMBA : Jurnal Ekonomi Pembangunan, Manajemen dan bisnis, Akuntansi, 2021)
This research purposes is to analyze the influence of ASEAN Corporate Governance Scorecard (ACGS) and ownership structure as represented by managerial ownership (KM) and institutional ownership (KI) on information asymmetric. This research uses sample of Kompas 100 index in Indonesia Stock Exchange (IDX) during 2013-2017 period. Based on purposive sampling method, the total of research sample are 52 companies with 5 year observation. This research is a quantitative research using multiple regression dummy variable analysis method. In the practice, statistic test is preceded by classical assumption test. The result of research show that partially ACGS has effect on information asymmetric, managerial ownership has no effect on information asymmetric, institutional ownership has no effect on information asymmetric and simultaneously the effect of ACGS and ownership structure as represented by KM and KI have effect on information asymmetric.